Prediction of corroding pipeline remaining life-time using semi-probabilistic approach - Noor, Norhazilan Md. (Faculty of Civil Engineering, 2009)
A semi-probabilistic methodology for predicting the remaining strength of submarine pipelines subjected to internal corrosion based on Recommended Practice RP-F101 by Det Norske Veritas (DNV) is described in this paper. It is used to estimate the maximum allowable operating pressure of the corroding pipelines based on series of pigging data, which represents the corrosion pit location and dimension. The introduction of partial safety factors in the DNV code to minimise the effect of uncertainties due to the defect sizing has improved the reliability of pipeline assessment methodology. Nevertheless, the code is still regarded as a fully deterministic approach due to its incapability of predicting the remaining life of corroded pipeline. Thus, we have added prediction capabilities to the capacity equation by introducing a standard deviation model of future defect depth. By doing so, the variation of safety factors of the capacity equation can be fully manipulated where prediction of future pipeline remaining life-time becomes feasible. The paper demonstrates calculation and prediction of pipeline remaining lifetime subjects to internal corrosion. The results shows the standard deviation of corrosion parameter affected the value of partial safety factor as corrosion progressing, hence amplify the conservatism of time to failure. In general, the prediction of pipeline remaining lifetime can effectively assist pipeline operators to evaluate future safe operating strategies including re-inspection and appropriate maintenance schedule. As a result it can minimize the possibility of pipeline failures until it reaches its designed lifetime.